재생온도가 저온인 경우 제습로터의 재생부/제습부 면적비율과 회전속도 최적화 - 정재동; 이대영; 윤석만 (대한설비공학회, 2007)
The desiccant rotor is the most essential component of desiccant cooling system, but its design relies on manufacturer’s experience and principles are not yet clear in spite of a lot of theoretical/experimental work published. The mathematical modeling of desiccant rotor needs solution of coupled partial differential equations of heat and mass transfer. In this study, numerical program is developed and validated using a real desiccant rotor. The calculation results are in reasonable agreement with the experimental data and other available numerical results. Optimization of desiccant rotor on the condition of low regeneration temperature are investigated. The optimal rotor speed at which the process outlet humidity becomes minimized, shows same as that of the system optimization. Compared to high regeneration temperature, broad is the range of optimal speed of low regeneration temperature. Systematic analysis on the optimal area ratio of regeneration to dehumidification section has also been conducted.